Timing Is Everything—The High Sensitivity of Avian Satellite Cells to Thermal Conditions During Embryonic and Posthatch Periods - Halevy, Orna (Frontiers in Physiology, 2020)
Myofiber formation is essentially complete at hatch, but myofiber hypertrophy increases posthatch through the assimilation of satellite cell nuclei into myofibers. Satellite cell proliferation and differentiation occur during the early growth phase, which in meat-type poultry terminates at around 8 days posthatch. Thus, any factor that affects the accumulation of satellite cells during late-term embryogenesis or early posthatch will dictate long-term muscle growth. This review will focus on the intimate relationship between thermal conditions during chick embryogenesis and the early posthatch period, and satellite cell myogenesis and pectoralis growth and development. Satellite cells are highly sensitive to temperature changes, particularly when those changes occur during crucial periods of their myogenic activity their myogenic activity. Therefore, timing, temperature and duration of thermal treatments have a great impact on satellite cell activity and fate, affecting muscle development and growth in the long run. Short and mild thermal manipulations during embryogenesis or thermal conditioning in the early posthatch period promote myogenic cell proliferation and differentiation, and have long-term promotive effects on muscle growth. However, chronic heat stress during the first 2 weeks of life has adverse effects on these parameters and may lead to muscle myopathies.